1998
DOI: 10.1055/s-2007-971899
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Medulla Responsiveness to the Sympathetic Nervous Activity in Sprinters and Untrained Subjects During a Supramaximal Exercise

Abstract: The purpose of this study was to compare the adrenal medullar responsiveness to the sympathetic nervous activity between sprinters and untrained subjects after a supramaximal exercise (Wingate-test). Thirteen subjects took part in this study: 7 male athletes (20.3+/-1.8 years) competing in sprint running (S) and 6 untrained men (UT) (21+/-1.3 years). They performed an incremental treadmill test to determine the maximal oxygen uptake (VO2max), a force-velocity test and a Wingate-test on 3 different days, separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
4
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 2 publications
7
41
4
1
Order By: Relevance
“…When compared to the values usually reported for French sportsmen (Zouhal et al 1998), these results indicate that our subjects were not highly trained in either endurance or sprint exercises. The W max developed and the high La max values [15.5 (0.8) mmolAE l )1 ] measured in capillary blood at the third minute following the end of the Wingate test confirmed that all subjects performed a supramaximal anaerobic effort.…”
Section: Physiological Characteristics Of the Subjectssupporting
confidence: 71%
See 4 more Smart Citations
“…When compared to the values usually reported for French sportsmen (Zouhal et al 1998), these results indicate that our subjects were not highly trained in either endurance or sprint exercises. The W max developed and the high La max values [15.5 (0.8) mmolAE l )1 ] measured in capillary blood at the third minute following the end of the Wingate test confirmed that all subjects performed a supramaximal anaerobic effort.…”
Section: Physiological Characteristics Of the Subjectssupporting
confidence: 71%
“…The Wingate test is well known to elicit anaerobic lactic metabolism, as evidenced by the high blood lactate values measured. The autoxidation of catecholamine might also contribute more to the oxidative stress induced by short-term supramaximal anaerobic exercise, since very high levels of catecholamine have been measured after such exercise (Zouhal et al 1998). Finally, the last and probably major factor might be the activation of the xanthine oxidase system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations